Ett vackert lidande - Anna Johansson (Kulturella Perspektiv, 2004)
In this article I discuss how a certain mood — in this case a complex one, summarized in the word suffering — takes material, physical and linguistic shape, and how the feeling, expressed through certain aesthetics, becomes the means for social positioning. My focus is on young people in specific subcultures, where suffering is regarded as something attractive and desirable. Giving physical shape to suffering is for these people a way to present themselves as unique and different from the mainstream culture with its "superficial happiness". At the same time, there is a hierarchy within these subcultural settings, where the ones with the most "cred" have the highest rank. Cred is a sort of symbolic capital which is principally about being authentic. To stand out as suffering in an authentic way, you need to find a balance between showing too much or too little. Irony is an important part of this balancing act.